Durability of components of FRP-concrete bonded reinforcement systems exposed to chloride environments. (1st January 2022) - Li, Jianglin; Mai, Zihua; Xie, Jianhe; Lu, Zhongyu
Abstract: Using fibre-reinforced polymer (FRP) composites as externally bonded reinforcements to retrofit concrete structures has been considered a promising strengthening technique. For the safe and economic use of externally bonded FRP reinforcement in coastal areas, the effects of long-term exposure to environmental chloride on the properties of FRP-concrete bonded systems need to be properly understood. This study aims to investigate the durability of components of FRP-concrete bonded systems immersed in chloride solution. Two types of FRP (carbon FRP or CFRP and basalt FRP or BFRP) specimens, two types of epoxy resin/adhesive (with epoxy values of 0.40 and 0.53) specimens, and conventional concrete cylinders were prepared and then immersed in a laboratory-accelerated chloride solution with a chloride ion concentration of 5% at 40 °C. The effect of immersion time (90, 180, 270, and 360 days) on the residual mechanical properties of the components was examined. In addition, a modified model was presented and used to predict the tensile strength retention of the FRPs. The results show that with increasing immersion time, the tensile strength of CFRP first increased and then decreased, while that of BFRP almost monotonically decreased. CFRP exhibited significantly better chloride resistance than BFRP, and the strength retention of CFRP was approximately 160% higher than that of BFRP after 360 days of exposure. The epoxy resin with a lower epoxy value had better corrosion resistance, although it had a lower tensile strength in the ambient environment, than the epoxy resin with a higher epoxy value. The predictions of the presented model agree reasonably well with the test results from existing studies.